Brewing analysis and quality control: development of an undergraduate course and integration within a university fermentation science and technology curriculum - Strevey, Daniel, author; Avens, John S., advisor; Bunning, Marisa, advisor; Laybourn, Paul, committee member (Colorado State University. Libraries, 2020)
The development of the course FTEC 422 Brewing Analysis and Quality Control (BAQC) originated at Colorado State University to alleviate the lack of university level course offerings available to future brewing professionals in the United States; particularly a course that addressed the analytical and quality control aspects of beer production. At the time of development only one course was available in Fermentation Science and Technology (FTEC) at CSU, with one more course in the planning stages. This indicated a lack of educational opportunities to support a quickly growing brewing industry of 2,051 breweries in the U.S. as of April 2012 (Gatza, 2012). In 2018 there where 7,346 breweries and more than 500,000 industry jobs (Watson, 2018). BAQC was designed to introduce and educate students in quality analysis and control topics related to the brewing industry through weekly lecture, lab exercises, and industry related field trips. BAQC was first offered as a pilot course in the spring semester of 2012 as FTEC 480 (Year 1 n=8), then again in spring 2014 as FTEC 422 (Year 2 n=12). During both years, the course had a set enrollment limit of 20 students. Instructor approval was required for student admittance in both years. As a result, registered students represented a diverse demographic of science disciplines. In Year 2, the course included students enrolled in the newly formed Fermentation Science and Technology Bachelors of Science degree. BAQC was designed to be a foundational course within the new major. Statistical analysis was used to determine if students' education backgrounds would have an impact on their success in the class. Results did not indicate that a student enrolled in a differing degree program would do better or worse in BAQC (P = 0.80). This result was somewhat expected since instructor approval was required for admittance. As a result some students were excluded from the course who may have performed poorly. An open admittance policy could have produced different results. Course evaluation forms were completed by students at the end of the semester with overwhelmingly positive feedback. BAQC offered a unique educational opportunity by providing students with applied technical experience preparing them for a fruitful career in the brewing industry. Brewing industry growth between 2012 and 2018 indicated strong growth will be sustained into the future, supplying an expanding number of industry jobs. BAQC also provides students a basic understanding of quality control and analysis objectives needed for other fermented food industry products such as cheese, yogurt, and baked foods. As the brewing industry had grown, a greater focus on quality products has emerged, according to relevant industry sources. Offerings within the Brewers Association, American Society of Brewing Chemists, Masters Brewers Association of the Americas, and Institute of Brewing and Distilling support beer quality control and analysis through publications and forums. These industry sources allow students who have completed BAQC to stay abreast of new developments in the knowledge and skills provided in this course. BAQC is now an integral part of the Fermentation Science and Technology degree offered at CSU. Through course evolution by new instructors BAQC will continue to stay relevant.